Growth and the Public Sector: A Critique of the Critics - Stefan Fölster; Magnus Henrekson (The Research Institute of Industrial Economics (IUI), 1997)
In a recent review article Jonas Agell, Thomas Lindh and Henry Ohlsson (1997) claim that theoretical and empirical evidence does not allow any conclusion on whether there is a relationship between the rate of economic growth and the size of the public sector. They illustrate their conclusion with simple cross-country regressions where the relation between growth and public expenditure tilts from negative to positive when control variables are introduced. In our article we argue that Agell, Lindh and Ohlsson base their conclusion on empirical studies, and on their own regressions, without evaluating the econometric problems that arize. We extend Agell et al.'s review in order to highlight some of these problems. Furthermore, we present evidence showing that once a number of econometric issues are dealt with the relationship between growth and public expenditure may be more robustly negative than it first appears.
Keywords: E62; H20; H50; O23; O40; 330; Economic growth; Government expenditure; Public sector; Taxation; Cross-country regressions.; Wirtschaftswachstum; Öffentlicher Sektor; Schätzung; OECD-Staaten